Pengaruh Indeks Sinkronisasi dalam Rumen pada Ransum Berbasis Bagase terhadap Produksi VFA Rumen pada Domba - Novi Eka Wati (Wahana Peternakan, 2017)
The aim of the research was to study the effects of synchronization index in the sugarcane bagasse based ration on acetate, propionate and butirate production of sheep. Two permanent cannulated male local sheep was 2 years old for sampling rumens fluids. They were feed a complete feed based on bagasse with a level of synchrony index 0,37; 0,50; 0,63 were design isoprotein and isoenergy. Each experimental diet was offered to each sheep three times randomly for 7 days, with 7 days interval between feeding period of each experimental diet. About 10 ml of rumen fluid sample were collected before feeding and 3 hour after feeding at the 7th day of each feeding trial period. The alteration of synchronization indexs did not affect acetate, propionate, butirate and ratio acetate/propionate (C2/C3) in rumen before feeding and 3 hour after feeding. Key words : acetate, butirat, propionate, synchrony index